Evaluation of estrogen-like activity on sewage treatment processes using recombinant yeast - Onda, K (Water science and technology : a journal of the International Association on Water Pollution Research, 2002)
Four sewage treatment plants based on an activated sludge process and a pilot scale plant for advanced sewage treatment located in Japan were evaluated for removal of estrogenic substances using in vitro recombinant yeast assay and chemical analysis. The results indicated that 17beta-estradiol (E2) significantly contributed to estrogen-like activity analyzed by yeast assay especially in secondary treated effluents. On the other hand, batch study showed that estrogen-like activity of spiked E2 was easily decreased by an activated sludge treatment. This result suggested that E2 concentrations measured by enzyme immunoassay (EIA) were interpreted as false positives in effluents, and that unknown estrogenic substances other than E2 might have contributed to estrogen-like activity in the secondary treated effluents. Further, in the pilot scale study, advanced sewage treatment processes such as a biological aerated filtration (BAF) process, an advanced oxidation process (AOP), were effective for the removal of those estrogenic activities contributed by unknown estrogenic substances in sewage secondary treated effluent